Description of a novel coprophilous Lichtheimia (Mucoromycotina , Mucorales) species with notes on Lichtheimia species and an identification key for the genus - da Cruz, Mateus Oliveira [UNESP]; Lee, Hyang Burm; Cordeiro, Thalline Rafhaella Leite; dos Santos, Francisca Robervânia Soares; Alves, Maria Helena; Nguyen, Thuong Thuong Thi; Gentekaki, Eleni; Hurdeal, Vedprakash G.; de Azevedo Santiago, André Luiz Cabral Monteiro (Springer Nature, 2024)
During the assessment of coprophilous mucoralean diversity in northeastern areas of Brazil, a Lichtheimia-like specimen (URM 8358) was isolated from rabbit dung. It was characterized based on morphological, physiological, and molecular analyses of the internal transcribed spacer (ITS), large subunit ribosomal (LSU) and actin DNA sequences. These analyses revealed a novel Lichtheimia species, which is described herein. The novel species forms abundantly branched sporangiophores, with most branches arising near the main sporangia, various-shaped columellae, and irregularly shaped sporangiospores. Furthermore, this manuscript provides notes of all Lichtheimia species, and an identification key for the genus is provided. These findings contribute to the existing knowledge on the taxonomy and distribution of Lichtheimia. Because of the clinical relevance of other Lichtheimia species, we encourage future research to determine whether URM 8358 can be pathogenic to humans.
Keywords: 1 new species; Lichtheimiaceae; rDNA; Taxonomy; Zygospores